(untitled) (Texas Journal of Engineering and Technology, 2026)
ISO 22000:2018 specifies requirements for a Food Safety Management System (FSMS) for organizations in the food chain and integrates Codex and HACCP principles. This paper aims to systematize quality and safety criteria for food products using clear indicators and limit values, assess drivers that influence FSMS performance, and propose a composite FSMS Performance Index (FSMS-PI) based on key performance indicators (KPIs). The methodology was built on the Codex CXC 1-1969 (Rev. 2020) GHP/HACCP approach, ISO/TS 22002-1:2009 prerequisite programme (PRP) requirements, and limit values from relevant product standards. As illustrative objects, a criteria registry was developed for wheat flour and refined vegetable oil. For wheat flour, moisture content ≤15.5% (m/m) was selected as a core quality indicator. For refined vegetable oils, acid value ≤0.6 mg KOH/g, peroxide value (PV) ≤10 meq O₂/kg, and limits for Cu ≤0.1 mg/kg and Fe ≤1.5 mg/kg were set as baseline indicators